Enhancing Supply Chain Performance through Logistics Integration and Third-Party Logistics (3PL) Competence: A Relational and Dynamic Capability Perspective in Ghana’s Cocoa Industry - George Agyenim BOATENG (PT Keberlanjutan Strategis Indonesia, 2025)
The study examines the relationship between logistics integration, third-party logistics (3PL) competence, and organisational performance in Ghana's cocoa industry, using the Relational View (RV) and Dynamic Capability Theory (DCT) as theoretical frameworks. It investigates how inter-firm relationships and adaptive capabilities influence logistics outcomes. A quantitative approach was employed, with data collected from 989 respondents across Licensed Buying Companies, haulage providers, and warehousing firms. Analysis using descriptive statistics, confirmatory factor analysis (CFA), and structural equation modelling (SEM) revealed significant positive relationships between internal and external logistics integration factors—such as information sharing and IT capabilities—and 3PL competence. Internal and external IT capabilities had the strongest impacts, while transportation sharing showed no significant relationship. Warehousing and distribution sharing positively influenced 3PL competence. The study concludes that logistics integration, supported by competent 3PL providers, enhances organisational performance by improving supply chain efficiency, reducing costs, and increasing customer satisfaction. The integration of RV and DCT provides a comprehensive understanding of how relational mechanisms and dynamic capabilities drive superior logistics outcomes. Future research should explore sector-specific variations, emerging technologies, and long-term impacts of logistics integration in diverse contexts. This study contributes to supply chain management literature by offering insights into logistics integration and 3PL competence, benefiting both researchers and practitioners.